Analgesic Efficacy of High‐Frequency Spinal Cord Stimulation: A Randomized Double‐Blind Placebo‐Controlled Study. Issue 4 (20th February 2013) - Perruchoud, Christophe; Eldabe, Sam; Batterham, Alan M.; Madzinga, Grace; Brookes, Morag; Durrer, Anne; Rosato, Marilu; Bovet, Nora; West, Samantha; Bovy, Michèle; Rutschmann, Blaise; Gulve, Ash; et al.
<x xml:space="preserve">Abstract</x> Introduction Spinal cord stimulation is a recognized treatment of chronic neuropathic and vascular pain. Recent data suggest that the use of very high‐frequency (HF) stimulation modes does produce analgesia without paresthesia. Aim of the Study To compare the efficacy of HF stimulation (HF spinal cord stimulation [HFSCS]) and sham stimulation on the patient's global impression of change (PGIC), pain intensity, and quality of life. Patients and Methods Forty patients who have achieved stable pain relief with conventional SCS have been recruited. After randomization, HFSCS and sham are initiated in a double‐blind randomized two‐period‐crossover design. Results Complete data were available from 33 patients. The primary outcome was a minimal improvement in the PGIC. The proportion of patients responding under HFSCS was 42.4% (14/33 patients) vs. 30.3% (10/33 patients) in the sham condition. The mean benefit of HF vs. sham was not statistically significant with a proportion of 11.2% in favor of HFSCS (p = 0.30). There was a highly statistically significant "period effect, " irrespective of treatment received, with 51.5% of patients (N = 17) improving at visit 3 vs. 21.2% (N = 7) at visit 5 (p = 0.006). The mean pain visual analog scale (VAS) on sham was 4.26 vs. 4.35 on HFSCS (p = 0.82) and the mean EuroQol five‐dimensional (EQ‐5D) index with HFSCS was 0.480 vs. 0.463 with sham (p = 0.78). Conclusion This is the first randomized double‐blind study on SCS. HFSCS was equivalent to sham for the primary outcome (improvement of PGIC) as well as for both the secondary outcomes (VAS and EQ‐5D index). There was a highly statistically significant "period effect" (p = 0.006) with improved PGIC scores in the first study period regardless of the treatment. The same trend was seen for VAS and EQ‐5D. It appears that the effect of HFSCS and sham is equal and only the order in the sequence, not the nature of the treatment, seems to dictate the effect.